Does Mild to Moderate Renal Dysfunction in Non-Dialysis Dependent Patients - Sazzad, Md Faizus; Yasmin, Farzana; Salekin, Mohammad Serajus; Musa, Shamsul Arif Md; Saklayen, SMG; Hoque, Anamul; Siraj, Masoom (Journal of Surgical Sciences, 2020)
Objectives: Algorithms of risk stratification for coronary artery bypass grafting (CABG) do not include a weighting for preoperative mild to moderate renal impairment defined as a serum creatinine 130 to 199mmol/L, which may impact mortality and morbidity after CABG. Hence our first objective was to ascertain the effect of a mild-to-moderate elevation in the preoperative serum creatinine level on post-operative outcomes. Our second objective was to ascertain which patient variables contributed to an increase in the serum creatinine level in association with coronary artery bypass grafting. Materials and methods: We reviewed the prospectively collected data from the cardiac surgical database, which holds clinical information on all the patients undergoing cardiac surgery at our department since July 2014 to June 2017. A total of 101 patients who had known pre-existing mild to moderate renal disease and who were undergoing first-time coronary artery bypass grafting with cardiopulmonary bypass were recruited for the study. Patients were divided, based on preoperative serum creatinine level, into 3 groups as follows: Group A: creatinine level of less than 130μmol/L; Group B: creatinine level of 130 to 159μmol/L; and Group C: creatinine level of 160μmol/L or greater. Result: Multivariate logistic regression showed that elevation of the preoperative serum creatinine level to 130μmol/L or greater increased the likelihood of hemodialysis postoperatively (P<0.001), as well as the need for postoperative ICU stay (P<0.001). Other factors contributing to a prolonged ICU stay were being 60 years of age or older (P=0.007), having a preoperative left ventricular ejection fraction of less than 40% (P=0.001), and having a prolonged cardiopulmonary bypass time (P< 0.001). In-hospital mortality was also significantly elevated in Group B and Group C; P=0.045 and <0.001 respectively with a few factors contributing to an increase in mortality on multivariable analysis were being female (P<0.001), being 60 years of age or older (P=0.004), having a preoperative left ventricular ejection fraction of less than 40% (P=0.006), and having a prolonged cardiopulmonary bypass time (P<0.001). Of particular note, the method of myocardial protection (cardioplegia with or without topical cooling) did not significantly influence in-hospital mortality, need for mechanical renal support, or ICU stay. Conclusions: Mild to moderate renal dysfunction is an important predictor of outcome in terms of inhospital mortality, morbidity, and midterm survival in patients undergoing CABG. As the preoperative serum creatinine level increases further (³160 μmol/L), this effect is more pronounced. Journal of Surgical Sciences (2018) Vol. 22 (2) : 104-109